Effectiveness of Outdoor Environmental Education Programme for Enhancing Responsible Environmental Behaviour among Fifth Grade Students - Mehra, Vandana; Kaur, Manpreet (INDIAN EDUCATIONAL REVIEW, 2012)
The present study was conducted to study the effect of outdoor environmental education programme for enhancing responsible environmental behaviour among fifth grade students of high, average and low intelligence. One hundred twenty fifth grade students belonged to two schools of Gurdaspur. The data were analysed with the help of 2-way Analysis of Variance. The major findings of the study were (a) Students taught environmental education by the outdoor environmental education programme exhibited better mean gains on responsible environmental behaviour and its dimensions as compared to students of control group who were taught environmental education by traditional method of instruction. (b) Students with high, average and low intelligence exhibited comparable mean gains on responsible environmental behaviour and its dimensions, locus of control, environmental attitude, beliefs and values related to the environment, environmental sensitivity, personal responsibility, environmental action strategies, and intention to act. (c) Students of high intelligence exhibited better mean gains on knowledge of ecological concepts and knowledge of environmental issues and problems than students with low and average intelligence.(d) Students of average intelligence group exhibited better mean gains on knowledge of environmental issues and problems as compared to students of lower intelligence. (e) There was significant interaction between treatment and levels of intelligence in relation to mean gains on knowledge of ecological concepts.